Generalized Contractive Set-Valued Maps on Complete Preordered Quasi-Metric Spaces - J. Marín; S. Romaguera; P. Tirado (Journal of Function Spaces and Applications)
By using a suitable modification of the notion of a w-distance we obtain some fixed point results for generalized contractive set-valued maps on complete preordered quasi-metric spaces. We also show that several distinguished examples of non-metrizable quasi-metric spaces and of cones of asymmetric normed spaces admit w-distances of this type. Our results extend and generalize some well-known fixed point theorems.